PENGARUH PEMBERIAN TONGKOL JAGUNG DALAM RANSUM TERHADAP PRODUKTIVITAS SAPI POTONG SIMENTAL: THE EFFECT OF GIVING CORN COBS IN THE RATIONAL ON THE PRODUCTIVITY OF SIMMENTAL BEEF CATTLE - Cahyono, Bayu; Purwadi, Purwadi; Wulandari, Eudia Christina (Universitas Boyolali, 2023)
ABSTRACT The aim of this research was to determine the effect of giving corn cobs on the productivity of Simmental beef cattle. The material used in this study were 14 Simmental cattle with an average body weight of 428 ± 16.7 Kg (CV = 3.91%) and an average age - an average of 2 years. The method used was RAL with 2 treatments (P0, P1) with 7 replications. Research parameters are dry matter consumption, crude protein consumption, TDN consumption, daily weight gain, feed conversion, and feed cost per gain. Analysis of research results using the